Formation of Liquid Water Pathways in PEM Fuel Cells: A 3-D Pore-Scale Perspective. Issue 5 (6th March 2020) - Shrestha, P.; Lee, CH.; Fahy, K. F.; Balakrishnan, M.; Ge, N.; Bazylak, A.
Abstract : We investigated the 3-D pore-scale liquid water distribution within the cathode GDL via in operando synchrotron X-ray tomography during low current density fuel cell operation to capture the early appearance of liquid water pathways. We found that the invasion of liquid water into the GDL only partially filled certain GDL pores. Liquid water preferentially flowed along some GDL fibers, which was attributed to the hydrophilic nature of carbon fiber and the presence of pore-scale mixed wettability within the GDLs.